Preliminary Screening of Antioxidant and Antibacterial Activities and Establishment of an Efficient Callus Induction inCurculigo latifoliaDryand (Lemba) - Farzinebrahimi, R.; Taha, Rosna Mat; Rashid, K.A.; Ahmed, B.A.; Danaee, Mahmoud; Rozali, S.E. (Hindawi, 2016)
Leaf, seed, and tuber explants of C. latifolia were inoculated on MS medium supplemented with various concentrations of BAP and IBA, alone or in combinations, to achieve in vitro plant regeneration. Subsequently, antioxidant and antibacterial activities were determined from in vitro and in vivo plant developed. No response was observed from seed culture on MS media with various concentrations of PGRs. The highest percentage of callus was observed on tuber explants (94%) and leaf explants (89%) when cultured on MS media supplemented with IBA in combination with BAP. A maximum of 88% shoots per tuber explant, with a mean number of shoots (), were obtained on MS medium supplemented with combinations of BAP and IBA (2.5 mg L−1). The best root induction (92%) and mean number () from tuber explants were recorded on 2.5 mg L−1 IBA alone supplemented to MS medium. The higher antioxidant content (80%) was observed from in vivo tuber. However, tuber part from the intact plant showed higher inhibition zone in antibacterial activity compared to other in vitro and in vivo tested parts.